Heat integration for bio-oil hydroprocessing coupled with aqueous phase steam reforming - Shemfe, Mobolaji B.; Fidalgo Fernandez, Beatriz (Elsevier, 2015)
Optimized heat exchanger networks can improve process profitability and minimize emissions. The aim of this study is to assess the heat integration opportunities for a hypothetical bio-oil hydroprocessing plant integrated with a steam reforming process via pinch technology. The bio-oil hydroprocessing plant was developed with rate based chemical reactions using ASPEN Plus® process simulator. The base case is a 1600 kg/h bio-oil hydroprocessing plant, which is integrated with a steam reforming process of the bio-oil aqueous phase. The impact of the reformer steam to carbon ratio on energy targets was analysed, revealing that significant energy savings can be achieved at different process variations. Aspen Energy Analyzer™ was employed to design the heat exchanger network. Two heat exchanger network designs are considered. The optimum design reveals that the second hydrodeoxygenation reactor effluent can preheat the bio-oil feed with minimal capital cost implication and achieve similar energy targets compared with the alternative design. The economic and environmental implications of the two heat exchanger network designs on product value were also evaluated.
Keywords: Biorefinery; Heat integration; Fast pyrolysis; Steam reforming; Pinch analysis